Paragraph writing : - Zemach, Dorothy E. (Macmillan, 2005)
This books is designed to help low-intermediate students analyze model paragraphs, find ideas for their writing, put their ideas into sentences, organize their sentences into paragraphs, review their paragraphs, and revise their paragraphs so that they become even stronger. This process approach to writing will not only develop your students' paragraph writing skills, but will also encourage them to become independent and creative writers.